Determinant factors and foreign direct investment in Malaysia cointegration and causality analysis - Chin Shing Yee; Mori Kogid; Borhan Abdullah; Jaratin Lily; Izaan Jamil (Penerbit Universiti Malaysia Sabah, 2025)
This research attempts to examine the determinants of FDI in Malaysia. The infrastructure, market size, exchange rate and inflation rate are considered independent factors that impact the FDI in this research. Yearly data from 1991 to 2020 was sourced from World Bank. The ARDL model was used to test the cointegration and causal relationship between the determinants and FDI. Based on the results, the infrastructure has positively influenced the FDI in the long and short run. The impact of market size, exchange rate and inflation rate on FDI is statistically insignificant in the long run. However, the market size and exchange rate have a significant short run relationship with FDI but none between the inflation rate and FDI. This research provides decision-making insights for investors, policymakers and practitioners. It plays a vital role in formulating FDI related policy in Malaysia. Despite facing limitations, this research concluded with some recommendations for future research.